An EU-China trade dialogue: A new policy framework to contain deteriorating trade relations - Iana Dreyer; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2008)
EU-China trade and economic relations have deteriorated. The rhetoric has become tougher on both sides, and the EU has imported the culture of "China bashing" from US politics. Increasingly hostile rhetoric and the danger of tit-for-tat protectionism are reason enough to establish a new process for bilateral trade relations. This Policy Brief assesses the opportunities to improve the souring economic relations between Europe and China offered by a new initiative to solve commercial problems and negotiate deeper integration: the EU-China High Level Trade and Economic Dialogue. The format of this dialogue is due to be announced in Beijing on the 24th of April 2008. In their paper, Iana Dreyer and Fredrik Erixon draw conclusions from a parallel US China Strategic Economic Dialogue launched in 2006. They analyse the risks and constraints under which the new EU-China Dialogue will operate.
Keywords: 330; Außenhandel; Handelsliberalisierung; EU-Staaten; China